1988
DOI: 10.2527/jas1988.66170x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroxine and Growth Hormone Treatment of Dairy Cows on Milk Yield, Cardiac Output and Mammary Blood Flow

Abstract: Four cows received thyroxine injections (T4; 20 mg/d) and three cows received growth hormone injections (GH; 44 mg/d) for 4 d during successive 16-d experimental periods. Measurement was made of milk yield, protein yield, mammary tyrosine and phenylalanine uptake, blood plasma hormone concentrations, mammary blood flow and cardiac output. Milk yield increased by 25% with T4 and 21% with GH treatment. Milk protein content tended to decline during T4 treatment and increase following GH treatment. Cardiac output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
40
3
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 29 publications
11
40
3
2
Order By: Relevance
“…Moreover, with respect to hormones, the concentrations of insulinlike growth factor (IGF-I) have been observed to increase after rbST administration (Ronge and Blum, 1989), but the rbST-IGF axis seems strictly dependent on the cow's nutritional status (Burton et al, 1994;Ronge et al, 1988). Insulin increments due to rbST treatment were also observed (Ronge and Blum, 1989;West et al, 1991), while other authors showed variable insulin changes after rbST treatment (Davis et al, 1988;de Boer and Kennelly, 1989;French et al, 1990). Many other authors have reported small changes of insulin and thyroid hormone concentrations (Butterwick et al, 1989;Chilliard et al, 1989;Cissé et al, 1991), and Johnson et al (1991) observed a significant reduction of 3,5,3'-triiodothyronine (T3) and cortisol concentrations.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, with respect to hormones, the concentrations of insulinlike growth factor (IGF-I) have been observed to increase after rbST administration (Ronge and Blum, 1989), but the rbST-IGF axis seems strictly dependent on the cow's nutritional status (Burton et al, 1994;Ronge et al, 1988). Insulin increments due to rbST treatment were also observed (Ronge and Blum, 1989;West et al, 1991), while other authors showed variable insulin changes after rbST treatment (Davis et al, 1988;de Boer and Kennelly, 1989;French et al, 1990). Many other authors have reported small changes of insulin and thyroid hormone concentrations (Butterwick et al, 1989;Chilliard et al, 1989;Cissé et al, 1991), and Johnson et al (1991) observed a significant reduction of 3,5,3'-triiodothyronine (T3) and cortisol concentrations.…”
Section: Introductionmentioning
confidence: 82%
“…It can be suggested that the rise of T3 concentration could be linked to the marked rise in glucose concentration observed in late lactation only (Bertoni et al, 1983). Therefore, it is not surprising that in several studies the rbST treatment did not affect blood levels of thyroid hormones (Chilliard et al, 1989;Davis et al, 1988;Ronge and Blum, 1989); in fact, it may occur in some peculiar conditions only: i.e. low yielding cows in late lactation showing a strong rise of blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Calculations Mammary blood flow was calculated for all sheep on day 4 of the HEC, based on the method of Davis et al (1988), using AA A-V concentration difference and the Fick principle:…”
Section: Methodsmentioning
confidence: 99%
“…While exogenous Prl administration did not affect an established lactation in cattle (Plaut et al 1987), previous work with thyroprotein feeding and Ta injection have shown significant effects of thyroid hormones on milk production (Blaxter et al 1949;Davis et al 1988a). Thyroid hormones (TH) enhanced milk production for a short period of 2 to 3 mo; after that, milk production is depressed and milk yield further declined after cessation of treatment (Moore 1958;Thomas et al 1957 (Merrifield 1963) and purified by high performance liquid chromatography (Gaudreau et al 1985 Insulin-like growth factor I was analysed by double antibody radio-immunoassay according to the method described by Elsasser et al (1988) with modifications as described by Lapierre et al (1990).…”
mentioning
confidence: 99%
“…Based on the hormonal profile (Lacasse et al 1991) (Davis et al 1988a) and mammary glucose uptake (Davis et al 1988b) but GH also increases mammary acetate uptake (Davis et al 1988b) and IGF-I levels (Davis et al 1987) while TH increases mammary utilization of preformed long-chain fatty acid, glycolysis (Davis et al 1988b) and did not affect IGF-I level (Davis et al 1987 (Peel and Bauman 1987).…”
mentioning
confidence: 99%